(untitled) (Marketing Journal, 2025)
This article analyzes the effectiveness of economic mechanisms in the development of the transport and logistics system. The systemʼs condition was assessed based on LPI indicators. The importance of digital technologies and modeling methods in improving e fficiency was identified. The influence of regional and external factors was examined. Based on international experience, proposals adapted to national conditions were developed. The findings may serve as a theoretical and practical basis for ensuring the sustainable development of the transport and logistics sector.